(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2023)
Arsenic (As) is a broadly distributed toxic metalloid that accumulates in the environment through natural and anthropogenic sources. Numerous techniques were evolved for arsenic remediation from water including adsorption, flocculation, ion exchange and reverse osmosis. Due to the excessive affinity between iron and inorganic arsenic species, iron-based adsorption is an emerging technique for the remediation of arsenic-contaminated water and soil. Whereas iron (Fe) and nickel (Ni) belong to the same chemical group (VIIIB) in the periodic table, it is expected to get similar interaction of Ni with As. An in vitro incubation study and pot experiment were conducted to evaluate the effect of Nickel on mineral release patterns in soil and growth yield of kalmi (Ipomoea aquatica), red amaranth (Amaranthus sp.) and Spinach (Spinacia oleracea L.). Nickel was applied as different doses of Nickel of 10, 40 and 160 mg/kg respectively where As was applied with irrigation water at the rates of 1 mg/L and incubated at field moisture condition for 10, 20 and 30 days individually in different pots. Total organic carbon (C), total nitrogen (N), phosphorus (P), sulfur (S), potassium (K) and 0.1N HCl extractable arsenic (As), iron (Fe) contents were determined at 10, 20 and 30 days of incubation. The pot experiment was carried out in triplicates for 45 days till the plants were grown to maturity. The growth performance of plants and the remedial effect of Ni on As toxicity in soil and plant was examined. Nickel showed a significant impact on fresh and dry yield of three plants and an antagonistic relationship between Ni and As was also observed i.e., Ni in soil was found to lessen the availability of As in soil likewise its accumulation in plants. J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(2): 79-88